2004
DOI: 10.1074/jbc.m403897200
|View full text |Cite
|
Sign up to set email alerts
|

Directed Mutagenesis in Region 713-720 of Human Thyroperoxidase Assigns 713KFPED717 Residues as Being Involved in the B Domain of the Discontinuous Immunodominant Region Recognized by Human Autoantibodies

Abstract: Autoantibodies (aAbs) to thyroid peroxidase (TPO), the hallmark of autoimmune thyroid disease (AITD), recognize conformational epitopes restricted to an immunodominant region (IDR), divided into two overlapping domains A and B. Despite numerous efforts aimed at localizing the IDR and identifying aAb-interacting residues on TPO, only two critical amino acids, Lys 713 and Tyr 772 , have been characterized. Precise and complete delineation of the other residues involved in the IDR remains to be defined. By using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 52 publications
(95 reference statements)
0
18
0
2
Order By: Relevance
“…These regulatory proteins are expressed on NPA cell membrane and probably partially protect them from CDC. Combining the various human recombinants anti-TPO aAbs we selected by phage display and characterised in term of epitopes (Bresson et al, 2003(Bresson et al, , 2004Chapal et al, 2000;Rebuffat et al, 2006), could make it possible to improve complement activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These regulatory proteins are expressed on NPA cell membrane and probably partially protect them from CDC. Combining the various human recombinants anti-TPO aAbs we selected by phage display and characterised in term of epitopes (Bresson et al, 2003(Bresson et al, , 2004Chapal et al, 2000;Rebuffat et al, 2006), could make it possible to improve complement activation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Garcia et al (1998) investigated TPO expression in a series of thyroid tumours by immunostaining using the anti-TPO mAb47 . We have previously shown that lysine 713 has a critical function for TPO epitope recognition by mAb47 Bresson et al, 2004), which is probably strongly impaired by cross-linking of the amino acid on formaldehyde slide fixation. Czarnocka et al (2001) used a TPO capture method that has the advantage to preserve integrity of the antigen structure and thereby allows immunological detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative approaches are to identify and remove B-cell or T-cell epitopes (13)(14)(15)(16)(17). We have recently used a mouse model to identify the major B-cell epitopes in the PE38 portion of RITs made by our group (18).…”
mentioning
confidence: 99%
“…These regions were firstly defined in competition experiments with a panel of murine monoclonal antibodies and patient autoantibodies (5), and subsequent studies with recombinant human anti-TPO Fab fragments confirmed these findings (6,7). Numerous attempts have been made to identify the amino acids in the autoantibodies' epitopes (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18); however, to clearly interpret these data and arbitrate between some conflicting results, the determination of the three-dimensional structure of TPO in complex with various autoantibodies is needed.…”
Section: Introductionmentioning
confidence: 99%